Randomised clinical trial: the effects of Helicobacter pylori eradication on glandular atrophy and intestinal metaplasia after subtotal gastrectomy for gastric cancer. Issue 5 (3rd July 2013) - Cho, S.‐J.; Choi, I. J.; Kook, M.‐C.; Yoon, H.; Park, S.; Kim, C. G.; Lee, J. Y.; Lee, J. H.; Ryu, K. W.; Kim, Y.‐W.
Summary Background Helicobacter pylori eradication is recommended for early gastric cancer (GC) patients after resection. Aim To evaluate whether H. pylori eradication improves glandular atrophy and intestinal metaplasia (IM) in GC patients undergoing subtotal gastrectomy. Methods This randomised, double‐blind trial was performed in tertiary care setting. Distal GC patients with H. pylori infection were randomised to receive proton pump inhibitor‐based triple therapy or placebo. The histology was evaluated using the updated Sydney system before and at 36 months after surgery. The endpoints were the comparison of atrophy and IM score changes between the allocated groups and according to final H. pylori status. Results Overall, 190 patients were randomised to the treatment and placebo groups. For lesser curvature of the corpus, mean atrophy and IM scores did not differ between the treatment and placebo groups. However, the H. pylori‐eradicated patients had significantly lower mean scores than the H. pylori‐persistent patients regarding atrophy (0.55 ± 0.95 vs. 1.05 ± 1.10 respectively; P = 0.0046) and IM (0.66 ± 0.99 vs. 1.05 ± 1.16 respectively; P = 0.0284). The percentage change from baseline was more marked in the H. pylori‐negative than in the H. pylori‐positive groups (−58.6% vs. −11.0% for atrophy and −60.5% vs. −35.6% for IM respectively). For greater curvature, mean atrophy score was lower in the H. pylori‐negative group than in the H. pylori‐positive group (0.14 ± 0.50 vs. 0.41 ± 0.75 respectively; P = 0.0281). The percentage change was −36.4% vs. 86.3%. Conclusion Helicobacter pylori eradication in GC patients is beneficial, as reflected by lower scores of atrophy and IM at 36 months after subtotal gastrectomy. (ClinicalTrials.gov number, NCT01002443).